Kleptomania Induced by Venlafaxine - Kumi Sakurada; Masashi Nibuya; Kazuo Yamada; Seishu Nakagawa; Eiji Suzuki (Case Reports in Psychiatry)
Introduction. Kleptomania is an impulse-control disorder that results in an irresistible urge to steal. It is often observed as a comorbidity in patients undergoing pharmacological treatment for Parkinson’s disease. Recurrent shopliftings are also observed in the clinical course of frontotemporal dementia. Case Presentation. After successful treatment of severe depression with venlafaxine at a dose of 225 mg/day, a 54-year-old euthymic female patient exhibited recurrent stealing behavior. After the diagnostic exclusion of frontotemporal dementia, kleptomania induced by venlafaxine administration was suspected. The symptoms of kleptomania disappeared with the gradual decrease in the venlafaxine dosage to 37.5 mg/day. Discussion. Venlafaxine is a dual serotonin-norepinephrine reuptake inhibitor. We considered two possible mechanisms to explain the pathophysiology of kleptomania in the present case: (1) increased dopaminergic neural transmission due to the inhibited dopamine reuptake by the norepinephrine transporter with a high dose of venlafaxine or (2) enhanced serotonergic neural transmission by the inhibition of serotonin reuptake by venlafaxine. In past studies, five cases of impulse-control disorder induced by selective serotonin reuptake inhibitors have been reported. This is the fourth report of venlafaxine-induced kleptomania and highlights the importance of considering the possibility of a rare side effect of kleptomania induced by antidepressant.